Workplace Death at Sea: Chinese Surviving Families’ Experiences of Compensation Claims - Shan, Desai (Relations industrielles / Industrial Relations, 2017)
Seafaring remains one of the most adventurous yet dangerous forms of work. Compared to shore-based industrial workers, seafarers suffer a risk of fatality that is up to 11 times higher. Workplace fatality is proved to be harmful to the social, financial and health conditions of surviving families. Although there has been an increase in attention given to the improvement of seafarers’ health and working conditions at sea, the effects of death at sea on surviving families has remained neglected by both researchers and policymakers.Drawing on in-depth interviews conducted with eight surviving family members in 2013 and 2014, this study investigates seafarers’ surviving families’ experiences of raising death compensation claims in China, which has the world’s largest population of seafarers. The work-related fatalities occurred between 2005 and 2013. At the time of the study, 2.4 years had elapsed on average since the deaths took place. All research participants reported considerable difficulties in communicating with crewing agencies and contacting ship owners when making compensation claims.This study shows that surviving families are in a vulnerable position when in conflict with companies. It also reveals that weak state prevention forces surviving families to defend their rights through protests. The absence of regulation over organizations involved in foreign-related employment relationships exacerbates the economic loss and mental harm suffered by surviving families following the occurrence of workplace fatalities. Furthermore, current legal and administrative procedures are unable to restore justice and provide therapeutic help for surviving families. Consequently, surviving families have suffered considerable financial loss and additional psychological harm in claim processes.